Penggunaan Moving Average dan Exponential Smoothing untuk Memprediksi Kebutuhan Beras Raskin di Kota Banda Aceh - Heri Tri Irawan; Iing Pamungkas; Fitriadi Fitriadi; Arhami Arhami; Khairul Hadi; T.M Azis Pandria (Jurnal Optimalisasi, 2020)
This study uses moving average and exponential smoothing methods to predict the demand for Raskin rice in Banda Aceh. The Logistics Agency (Bulog) is a food institution in Indonesia that organizes a rice trading system, which functions to provide rice distribution services to the public. The fluctuation in demand for Raskin rice in Banda Aceh makes it difficult for Bulog to predict future needs. In addition, the excess supply of Raskin rice will also be very detrimental because rice is a staple that is perishable. Therefore, it is necessary to conduct research to predict the demand for Raskin rice in Banda Aceh. The results of forecasting or prediction by comparing two methods and three errors in forecasting accuracy, it can be concluded that the exponential smoothing method with α = 0.90 can be used to predict the demand for Raskin rice in Banda Aceh City. The prediction result of the demand for raskin rice in Banda Aceh is 92,407 tons, with an MAD error rate of 4.92, MSE 34.58, and MAPE 0.006%, or having the smallest value compared to the 7-month moving average method.